The impacts of political uncertainty on asset prices: Evidence from the Bo scandal in China - Liu, Laura Xiaolei; Shu, Haibing; Wei, K.C. John (Journal of Financial Economics, 2017)
Models of political risk predict that increases in political uncertainty cause stock prices to fall, especially for politically sensitive firms. We use the event of the Bo Xilai political scandal in 2012 in China as an exogenous shock to identify the impact of political uncertainty on asset prices. We document that the Bo scandal caused a significant drop in stock prices, especially for firms that are more politically sensitive. Further analysis shows that the stock price drop is mainly driven by a change in discount rate, providing strong support for the existence of priced political risk.